Web-Based Geographic Information System Design at Hospital Locations in Tangerang Regency - Kiki Vibrianasari; Adiyanto Adiyanto; Masduki Asbari (UJoST- Universal Journal of Science and Technology, 2022)
The health office is one of the supporting elements of hospitals in providing public services needed by the community, consisting of hospital services and other services to meet community needs in the health sector. Along with the increasingly vital function of hospitals, every community is expected to know the locations of the hospitals closest to their homes to anticipate things that are not desirable. The purpose of this study is to implement a Geographic Information System (GIS) as a system that can provide information about the location of the hospital. This system was developed using Google Maps API, PHP, and MySQL. Hospital facilities in the Tangerang district also make it easier for the Health Office to provide an assessment and quality of hospitals. To be able to provide information to users who want to find the locations of hospitals in the Tangerang district